Perceived Effects of Debates and Role-Playing in Active Learning among Grade 7 History Students - De Claro, Maureen; Geli, Princess Dae; Cabello, Cristina; Collado, Sherlyn; Maristela, Mary Jane; Canosa, Jamaica Maribeth; Bautista, Harren James; De Ramos, Lovelita; Hernandez, Lyra Crizelle (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the perceptions of Grade 7 History students toward debates and role-playing as learner-centered strategies and their relationship with active learning in History education. Conducted at Governor Feliciano Leviste Memorial National High School, the study used a descriptive research design with 163 respondents selected from a total population of 282 Grade 7 students through stratified random sampling using the Raosoft Sampling Calculator. Data were gathered through a survey questionnaire that assessed students’ perceptions of debates and role-playing and measured active learning in terms of physical, intellectual, and social engagement using a 4-point Likert scale. The instrument was developed from related literature and tested for reliability using Cronbach’s Alpha, while data were analyzed through weighted mean and Pearson’s R using the Statistical Package for the Social Sciences. Findings showed that students generally agreed that debates and role-playing were effective teaching and learning activities in History, with positive effects on empathy, collaboration, participation, communication, creativity, critical thinking, and peer interaction. Students also assessed their physical, intellectual, and social engagement to a great extent. Statistical results revealed a significant and strong positive relationship between students’ perceptions of debates and role-playing and their active learning, particularly in physical, intellectual, and social engagement. The study concluded that debates and role-playing promote meaningful, interactive, and student-centered History learning. It recommended the use of a proposed teaching guide to strengthen participation, collaboration, communication, critical thinking, and overall engagement in History classes. The study supports SDG 4, Quality Education, by promoting learner-centered and engaging instruction, and may also relate to SDG 16, Peace, Justice, and Strong Institutions, through History education’s contribution to civic consciousness, cultural identity, and nation-building. Its sustainability impact lies in strengthening educational and institutional practices by providing teachers, school administrators, curriculum developers, and future researchers with practical support for improving active learning in History.
Keywords: Active Learning; Debates; Grade 7 History; History Education; Learner-Centered Strategies; Role-Playing; Social Engagement; Student Engagement